2020
DOI: 10.1242/jcs.239277
|View full text |Cite
|
Sign up to set email alerts
|

AKT but not MYC promotes reactive oxygen species-mediated cell death in oxidative culture

Abstract: Oncogenes can create metabolic vulnerabilities in cancer cells. We tested how AKT (herein referring to AKT1) and MYC affect the ability of cells to shift between respiration and glycolysis. Using immortalized mammary epithelial cells, we discovered that constitutively active AKT, but not MYC, induced cell death in galactose culture, where cells rely on oxidative phosphorylation for energy generation. However, the negative effects of AKT were temporary, and AKT-expressing cells recommenced growth after ∼15 days… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
2
7
0
Order By: Relevance
“…But Subramaniam et al 25 observed high immunoglobulin G (IgG) concentrations in lactating sows and suckling piglets when fed with organic acid mixed diets. Thus, we speculated that the enrichment of galactaric acid in responders may be related to abnormal glucose or galactose metabolism in tumors, which was similar to the results reported by Zheng et al It could be attributed to the monophyly of the energy source pathways in tumor cells 26 . Notably, both Ruminococcus bromii and Ruminococcus callidus in human intestines can utilize galactose.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…But Subramaniam et al 25 observed high immunoglobulin G (IgG) concentrations in lactating sows and suckling piglets when fed with organic acid mixed diets. Thus, we speculated that the enrichment of galactaric acid in responders may be related to abnormal glucose or galactose metabolism in tumors, which was similar to the results reported by Zheng et al It could be attributed to the monophyly of the energy source pathways in tumor cells 26 . Notably, both Ruminococcus bromii and Ruminococcus callidus in human intestines can utilize galactose.…”
Section: Discussionsupporting
confidence: 85%
“…Ruminococcus was enriched in responders and positively correlated with serum galactaric acid and negatively correlated with formononetin in our study. At the species level, Ruminococcus bromii and lar to the results reported by Zheng et al It could be attributed to the monophyly of the energy source pathways in tumor cells 26. Notably, both Ruminococcus bromii and Ruminococcus callidus in human intestines can utilize galactose.…”
supporting
confidence: 56%
“…The complexes were also particularly active in the 3D model, a more reliable system compared to 2D, with the most promising activity shown by complexes 2 and 4 with a galactose substituent. The role of galactose in the metabolism of cancer cells is attracting significant attention because of potential diagnostic and therapeutic possibilities [ 40 , 41 ]. While the role of the free sugars as targeting vectors is not completely confirmed, the selectivity shown in 2D studies is a solid base to hypothesise that the carbohydrate moieties play an important role in targeted therapies.…”
Section: Discussionmentioning
confidence: 99%
“…The complexes resulted also particularly active toward CSCs (Cancer Stem Cells) with the most promising activity shown by complex 4 with a galactose substituent. The interplay of galactose in the metabolism of cancer stem cells is attracting high attention because of potential diagnostic and therapeutic possibilities ( Valle et al, 2020 ; Zheng et al, 2020 ). At the moment, it is not possible to affirm with certainty if the sugar in the complexes described herein is playing the role of active vector because more specific biological studies (beyond the scope of this work) should be conducted (i.e., inhibition of the GLUTs receptors), but it is clear that the presence of the sugar is increasing the anticancer activity and the drug internalization, as demonstrated with the uptake experiment in CSCs (this could be due to the higher lipophilicity).…”
Section: Discussionmentioning
confidence: 99%